Currency substitution and exchange rate volatility in Nigeria: An autoregressive distributed lag approach - Isaiah O. Ajibola; Sylvanus U. Udoette; Rabia A. Muhammad; John O. Anigwe (CBN Journal of Applied Statistics, 2020)
This study investigates the relationship between exchange rate volatility and cur-rency substitution in Nigeria, using Autoregressive Distributed Lag (ARDL) model.After accounting for the presence of structural breaks, evidence from the findingsshows that domestic interest rate and expected changes in exchange rate are impor-tant determinants of currency substitution. In addition, there is empirical supportfor a positive relationship between exchange rate volatility and currency substitu-tion both in the short- and long-run. This implies that higher real exchange ratevolatility is associated with an increased level of currency substitution. In view ofthese findings, the paper calls for sustained efforts by the monetary authority incontaining exchange rate volatility and inflation as a way of curbing the spate ofcurrency substitution in the country.
Keywords: C5; F3; F31; 330; Autoregressive distributed lag; currency substitution; exchange ratevolatility; structural breaks